2020
DOI: 10.1002/bdr2.1664
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diet as a risk factor for primary congenital glaucoma and defects of the anterior segment of the eye in the National Birth Defects Prevention Study

Abstract: Primary congenital glaucoma (PCG) and anterior segment defects (ASDs) are rare ocular malformations diagnosed early in life which can cause blindness. Pathogenic variants in several genes have been linked to these conditions, but little is known about nongenetic risk factors. We investigated the association between maternal nutrition and PCG and ASDs in the National Birth Defects Prevention Study, a large population‐based, multicenter case–control study of major birth defects in the United States. Mothers of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Inadequate maternal nutritional intake during pregnancy may lead to negative short- and long-term health consequences for both the mother and her child [ 7 , 8 , 9 ]. In the scientific literature, it is widely recognised that environmental factors such as diet during pregnancy can contribute to the development of certain diseases among offspring [ 10 , 11 , 12 , 13 , 14 ] as well as the occurrence of metabolic alterations (overweightness or obesity) in pregnant women, especially in early pregnancy, which increase the probability of obesity in their future children [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate maternal nutritional intake during pregnancy may lead to negative short- and long-term health consequences for both the mother and her child [ 7 , 8 , 9 ]. In the scientific literature, it is widely recognised that environmental factors such as diet during pregnancy can contribute to the development of certain diseases among offspring [ 10 , 11 , 12 , 13 , 14 ] as well as the occurrence of metabolic alterations (overweightness or obesity) in pregnant women, especially in early pregnancy, which increase the probability of obesity in their future children [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Folate as one of the colonic bacterial fermentation products is a powerful micronutrient with a broad spectrum of wellknown functions at various levels. Its importance in ocular health is well established [144][145][146][173][174][175][176][177][178][179], but its immunomodulatory properties represent an emerging concept for functional T reg stabilization. The colon is a significant folate depot [19] that participates in metabolism and contributes to bioavailable folate levels.…”
Section: Discussionmentioning
confidence: 99%
“…One study reported intake of total vitamin A from supplements only (Bille et al, 2007). Intake data were collected using validated or modified versions of validated FFQs in 15 studies (Beurskens et al, 2013;Botto et al, 2001;Carmichael et al, 2020;Carmichael et al, 2010;Chandler et al, 2012;Feldkamp et al, 2011;Johansen et al, 2008;Krapels et al, 2004;Moore et al, 2020;Obrycki et al, 2019;Shaw et al, 2010a;Shaw et al, 1997;Smedts et al, 2009;Wallenstein et al, 2013;Weber et al, 2018;Yang et al, 2008). Three studies used interviews (Martínez-Frías & Salvador, 1990;Mills et al, 1997;Mitchell et al, 2003).…”
Section: Case-control Studiesmentioning
confidence: 99%
“…Eight case-control studies reported preformed vitamin A intake from diet only (Botto et al, 2001;Chandler et al, 2012;Krapels et al, 2004;Moore et al, 2020;Obrycki et al, 2019;Smedts et al, 2009;Weber et al, 2018;Yang et al, 2008), whereas two studies reported preformed vitamin A intake from diet + supplements (Botto et al, 2001;Johansen et al, 2008). One study reported preformed vitamin A intake from liver and liver + supplements (Mitchell et al, 2003).…”
Section: Case-control Studiesmentioning
confidence: 99%
See 1 more Smart Citation